Fourth Order Schemes for Time-Harmonic Wave Equations with Discontinuous Coefficients (Communications in Computational Physics, 2018)
We consider high order methods for the one-dimensional Helmholtz equation and frequency-Maxwell system. We demand that the scheme be higher order evenwhen the coefficients are discontinuous. We discuss the connection between schemesfor the second-order scalar Helmholtz equation and the first-order system for the electromagnetic or acoustic applications.